2020
DOI: 10.1186/s12870-020-02517-x
|View full text |Cite
|
Sign up to set email alerts
|

New quantitative trait locus (QTLs) and candidate genes associated with the grape berry color trait identified based on a high-density genetic map

Abstract: Background: Berry color is an important trait in grapes and is mainly determined by the anthocyanin content and composition. To further explore the coloring mechanism of grape berries, the F1 population of Vitis vinifera 'Red Globe' × 'Muscat Hamburg' was used to map the color locus, and transcriptome analysis was performed to assist in screening candidate genes. Results: A total of 438,407 high-quality single-nucleotide polymorphisms (SNPs) were obtained from wholegenome resequencing (WGS) of the population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 63 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…Conclusively, this region could be involved in both berry skin firmness and berry skin elasticity. Thus, we assume that berry color locus, i.e., the presence of VvmybA1 and VvmybA2 ( Kobayashi et al, 2004 ; This et al, 2007 ; Pelsy et al, 2015 ; Röckel et al, 2020 ; Sun et al, 2020 ) could be one additional regulator that is involved in grape berry development. Looking into the confidence interval of 0.3 Mbp on LG2 within the reference genome PN40024 12x.V2 ( Table 2 ) has revealed several MYB-related genes and MYB90 transcription factors and polypeptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusively, this region could be involved in both berry skin firmness and berry skin elasticity. Thus, we assume that berry color locus, i.e., the presence of VvmybA1 and VvmybA2 ( Kobayashi et al, 2004 ; This et al, 2007 ; Pelsy et al, 2015 ; Röckel et al, 2020 ; Sun et al, 2020 ) could be one additional regulator that is involved in grape berry development. Looking into the confidence interval of 0.3 Mbp on LG2 within the reference genome PN40024 12x.V2 ( Table 2 ) has revealed several MYB-related genes and MYB90 transcription factors and polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…They also summarized that in addition to cutin and wax, the cuticle of many fruit species contains secondary metabolites like triterpenoids, sterols, alkaloids, and phenylpropanoids (flavonoids). MYB-type transcription factors regulate the biosynthesis pathways of flavonoid, anthocyanin, and proanthocyanidin in several plant species like maize, apple, and grapevine ( Röckel et al, 2020 ; Sun et al, 2020 ; Crespan et al, 2021 ). This is underlined by the observation of Ma et al (2020) that the MYB family, as one investigated transcription factor, has a potential effect on berry skin firmness.…”
Section: Discussionmentioning
confidence: 99%
“…Grapevine breeding and trait mapping have proceeded rapidly with the availability of genome sequences, molecular marker implementation and evolution, and increased use of interspecific crosses for the introgression of economic traits [ 6 ]. Berry skin color, a qualitative trait, has been mapped to a major locus on chromosome 2 and associated with MYBA1 gene [ 4 , 9 , 10 , 11 , 12 , 13 , 14 ]. Anthocyanins (concentration and type) influence berry color and contribute to wine quality and have been mapped to chromosome 2, 7, 12, 13, and 14 [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also identified new regions for already-studied traits, such as one involved in anthocyanin acylation and tri-hydroxylation on chromosome 13. This QTL was not detected neither in a Syrah x Pinot Noir progeny (Costantini et al 2015), nor in a Red Globe x Muscat of Hamburg progeny (Sun et al 2020), and is distinct from the functionally validated anthocyanin acyltransferase on chromosome 3 (Rinaldo et al 2015 Sep 22) or the Flavonoid 3ʹ,5ʹ-hydroxylase cluster located on chromosome 6. This region contains two WRKY transcription factors (Vitvi13g00189 and Vitvi13g01916) orthologuous of AtWRKY55 and AtWRKY54/70 (Wang et al 2014).…”
Section: Candidate Genes For Phenolic Compoundsmentioning
confidence: 76%